Catalog of the Chrysomelinae (Coleoptera: Chrysomelidae) deposited in the entomological collections of the Instituto Nacional de Pesquisas da Amazônia (INPA) and the Universidade Federal do Amazonas (UFAM), Manaus, Brazil, with an illustrated key for the genera occurring in Brazil (except Aeneolucentia, Jermaniella, and Pandona) - Sampaio, Aline; Fonseca, Claudio Ruy Vasconcelos Da (Zootaxa, 2023)
This paper presents a species catalog of leaf beetles of the subfamily Chrysomelinae (Coleoptera: Chrysomelidae) deposited in two important Brazilian institutions in the state of Amazonas (Instituto Nacional de Pesquisas da Amazônia and Universidade Federal do Amazonas), providing their respective type localities, geographic distributions, as well as illustrations for all listed species (including pictures of the types of Platyphora imperialis (Stål, 1858), Platyphora excellens (Stål, 1859), Platyphora sanguinipennis (Jacoby, 1895), and Platyphora olivenca (Bechyně, 1954)), and new locality records, predators, parasites, parasitoids, and host plant for some species. In addition, we provide the first illustrated key for the genera occurring in Brazil (except Aeneolucentia, Jermaniella, and Pandona).